Metacommunication and Laughter-Crying in Uzbek and English - qizi, Azimova Muxtasarxon Jaloldin; qizi, Abdurahmonova Kamola Rustam (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Metacommunication, the process of communicating about communication, plays a pivotal role in the way individuals interpret and respond to social interactions. Laughter and crying, as universal yet culturally nuanced emotional expressions, act as significant metacommunicative cues that transcend linguistic barriers while simultaneously embodying cultural specificity. This study explores the dual phenomena of laughter and crying within the framework of metacommunication in Uzbek and English linguistic and cultural contexts. By analyzing verbal and nonverbal patterns, we identify how these expressions convey meaning, regulate emotional resonance, and mediate interpersonal dynamics. In the Uzbek context, laughter and crying are deeply embedded in traditional social norms and collective cultural narratives, serving as markers of respect, humility, and shared experiences. In English-speaking cultures, these expressions often emphasize individual emotional states and personal boundaries, reflecting broader cultural inclinations towards individualism. Through comparative analysis, this paper investigates how these emotional responses are framed within metacommunicative acts, such as irony, sarcasm, or sincerity, and how they influence intercultural understanding.